A calibrated physical flow standard for medical perfusion imaging. (April 2021) - Kok, G.; Pelevic, N.; Chiribiri, A.; Milidonis, X.; Nazir, M.; Capstick, M.; Drost, S.; Poelma, C.; Schaeffter, T.
Abstract: In the medical sector, various imaging methodologies or modalities (e.g. MRI, PET, CT) are used to assess the health of various parts of the bodies of patients. One such investigation is the blood flow or perfusion of the heart muscle, expressed as the (blood) flow rate normalized by the mass of the volume of interest. Currently there is no physical flow standard for the validation of quantitative perfusion measurements. This need has been addressed in the EMPIR 15HLT05 PerfusImaging project. A phantom simulating the heart muscle has been developed with the capability that it can reproducibly generate a flow profile with individual flow rates known with a relative uncertainty of about 10% ( k  = 2) and total flow rate known with an uncertainty of 1% ( k  = 2). An overview of the phantom and its validation is given. Next, a new analysis method is presented to analyse the sequence of images which are acquired when using a standard dynamic imaging protocol. It is concluded that the new, alternative approach gives results comparable to the standard analysis method. Highlights: New flow standard/phantom for validating medical perfusion imaging. Calibration of phantom using different techniques. New flow model and data processing approach for quantifying perfusion. Comparison of perfusion quantification methods.